A soberania no banco dos réus: uma reflexão sobre o Tribunal Penal Internacional e justiça cosmopolita - Teixeira, Ana Cristina Nascimento Mandin (2006)
The topic to be developed in this dissertation - International Criminal Court (ICC) - spreads, as is evident in several branches of international law, particularly in criminal and criminal procedure, and relate closely to the rules of constitutional law, it always finds its foundation draws or validity of the Charter and the sources of International Law. Precisely for this peculiarity is that the question of sovereignty - much affection subject to international law as the study of International Relations - assumes an important role, since the emergence of the ICC influences the national states and their righteousness, they need to that harmonize, implementing principles and mechanisms that are theirs, aiming to single out this particular field ativdade court of law